Neural systems engaged by planning: a PET study of the Tower of London task. - Baker, S; Rogers, R; Owen, A; Frith, C; Dolan, R; Frackowiak, R; Robbins, T (1996)
The functional anatomy of planning was investigated using the Tower of London task. Activation was observed in a distributed network of cortical areas incorporating prefrontal, cingulate, premotor, parietal and occipital cortices. Activation in corresponding areas has been observed in visuospatial working memory tasks with the exception of the rostral prefrontal cortex. This area may be identified with the executive components of planning comprising response selection and evaluation. Enhanced neural activity in both this rostral prefrontal area and the visuospatial working memory system was associated with increased task difficulty.